Cinderella complex: Kecenderungan gangguan kepribadian dependen pada perempuan - Ain, Iftitah Yasmin Qurrotul (Maliki Interdisciplinary Journal, 2024)
Some parents raise their children based on gender standards. Since they were born, men are taught to be independent, they have been trained to standing up for himself and always think based on reality. In contrast, most women are educated to be soft, to be dependent on others, and many parents even build up the hope that one day in time, their little princess will find help from a handsome prince who will protect her all the time. This makes women live in their expectations and always depends on other people to achieve happiness, and has a fear of independence known as the cinderella complex. Cinderella complex is the inclination of woman that need to lean on someone, to be nurtured, and to be taken care of, especially from men. This article aims to explain cinderella complex syndrome related to dependent personality disorder.